SID-2 negatively regulates development likely independent of nutritional dsRNA uptake. Issue 6 (3rd June 2021) - Braukmann, Fabian; Jordan, David; Jenkins, Benjamin; Koulman, Albert; Miska, Eric Alexander
ABSTRACT: RNA interference (RNAi) is a gene regulatory mechanism based on RNA-RNA interaction conserved through eukaryotes. Surprisingly, many animals can take-up human-made double stranded RNA (dsRNA) from the environment to initiate RNAi suggesting a mechanism for dsRNA-based information exchange between organisms and their environment. However, no naturally occurring example has been identified since the discovery of the phenomenon 22 years ago. Therefore it remains enigmatic why animals are able to take up dsRNA. Here, we explore other possible functions by performing phenotypic studies of dsRNA uptake deficient sid-2 mutants in Caenorhabditis elegans . We find that SID-2 does not have a nutritional role in feeding experiments using genetic sensitized mutants. Furthermore, we use robot assisted imaging to show that sid-2 mutants accelerate growth rate and, by maternal contribution, body length at hatching. Finally, we perform transcriptome and lipidome analysis showing that sid-2 has no effect on energy storage lipids, but affects signalling lipids and the embryo transcriptome. Overall, these results suggest that sid-2 has mild effects on development and is unlikely functioning in the nutritional uptake of dsRNA. These findings broaden our understanding of the biological role of SID-2 and motivate studies identifying the role of environmental dsRNA uptake.